The Social Support and Assertive Behavior of Students - Fahmi, Reza; Aswirna, Prima (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2020)
Humans are social creatures who need mutual support from one another. So social support contributes to their assertive behavior in social life. Furthermore, this study wants to examine the close relationship between social support and assertive behavior among students The purpose of this study is to explain the categories of social support, certain behavior categories, and the relationship between social support and assertive behavior of students majoring in Islamic Counseling Guidance Imam Bonjol Padang. The research method used is a quantitative research method with correlation techniques that are processed with the SPSS program version 16.0 for windows. The population in this study was 334 students majoring in Islamic Counseling Guidance for Imam Bonjol Padang, with 182 students as the research sample. The sample was taken using proportionate stratified random sampling. Data collection techniques used in this study are psychological scales, which are guided by the Likert model scale. The data analysis technique used is the Pearson correlation. The results showed that 64.3% of students had high social support, and 73.1% of students showed low assertive behavior. The results showed relations between social support and assertive behavior. Copyright © 2020. Psikoislamika: Jurnal Psikologi dan Psikologi Islam